Controversies in Podocyte Loss: Death or Detachment? - Yin, Lijun; Yu, Lu; He, John Cijiang; Chen, Anqun (Frontiers in Cell and Developmental Biology, 2021)
Glomerular podocytes are characterized by terminally differentiated epithelial cells with limited proliferating ability, thus podocyte loss couldn’t be fully compensated by podocyte regeneration. A large body of clinical studies collectively demonstrated that podocyte loss correlated with glomerular diseases progression. Both podocyte death and podocyte detachment attribute to podocyte loss, however, which one is the main cause remain controversial. Up to date, multiple mechanisms are involved in the podocyte death including programmed apoptotic cell death (apoptosis and anoikis), programmed non‑apoptotic cell death (autophagy, entosis, and podoptosis), immune‑ related cell death (pyroptosis), and other types of cell death (necroptosis and mitotic catastrophe related cell death). Apoptosis is considered as a common mechanism of podocyte loss, however, most of the data were generated in vitro, and the evidence of in vivo podocyte apoptosis is limited. The isolation of podocytes in the urine and subsequent culture of urinary podocytes in vitro suggest detachment of viable podocytes could be another important mechanism for podocyte loss. In this review, we summarize recent advances that address this controversial topic on the specific circumstances of podocytes loss.